USING OF INTONATION IN LEARNING ENGLISH LANGUAGE - Sharipova, Feruza Negmatullaevna (Innovative Development in Educational Activities, 2023)
Intonation is a universal language. There are no spoken languages in which the prosodic parameters do not change, but intonation works differently in different languages. Instead of focusing on what we say, it’s about how we say it. It is impossible to comprehend the thoughts and expressions that accompany words if intonation is absent. Since it is a feature of every language, the idea we are presenting is not novel. However, intonation suffers when students are too preoccupied with finding their words. All languages share an aspect of pronunciation known as intonation. Stress, rhythm, connected speech, and accent are additional characteristics of pronunciation.